Pro ASP.NET 2.0 E-Commerce in C# 2005 - Sarknasp, Paul (Apress, 2012)
In this book, I will use a real-world example to demonstrate how to construct a multitiered ASP.NET application that allows a business to sell its merchandise online. Using this real-world, case-study approach, the discussion will start with gathering the requirements. Then I’ll go into designing and modeling the database, building the architecture, completing the code base, and finally compiling and deploying the production environment. By following the case study in this book, you will be able to use the skills you’ve learned to expand a company’s customer base and sell products online, thus increasing the company’s profitability..